Innovations in Transport Success, Failure and Societal Impacts - van Wee, Bert; Annema, Jan; Köhler, Jonathan (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This timely book explores the likely success or failure of potential transport innovations. Chapters examine societally relevant effects of transport innovations, including impacts on the environment, accessibility, safety and more. It focuses on complex innovations in which both public and private actors are involved.